The fortunes of adolescent mother and their children : The transmission of poverty in Santiago, Chile - Buvinic, M.; Valenzuela, J. P.; Molina, T.; González, Edelmira
tbls.
pp. 269-297
Keywords: Chile; Pobreza; Madres Adolescentes